2015
DOI: 10.1101/gad.264192.115
|View full text |Cite
|
Sign up to set email alerts
|

MERIT40 cooperates with BRCA2 to resolve DNA interstrand cross-links

Abstract: MERIT40 is an essential component of the RAP80 ubiquitin recognition complex that targets BRCA1 to DNA damage sites. Although this complex is required for BRCA1 foci formation, its physiologic role in DNA repair has remained enigmatic, as has its relationship to canonical DNA repair mechanisms. Surprisingly, we found that Merit40 −/− mice displayed marked hypersensitivity to DNA interstrand cross-links (ICLs) but not whole-body irradiation. MERIT40 was rapidly recruited to ICL lesions prior to FANCD2, and Meri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 69 publications
2
26
0
Order By: Relevance
“…Together, the FA/BRCA proteins and associated factors form a multifunctional network that plays a critical role in managing various forms of DNA damage and replication stress (10). Although both FA and BRCA proteins are required for ICL repair, each pathway also supports nonoverlapping functions (11,12) that play different roles in how cells respond to treatment with DNA cross-linking agents.…”
mentioning
confidence: 99%
“…Together, the FA/BRCA proteins and associated factors form a multifunctional network that plays a critical role in managing various forms of DNA damage and replication stress (10). Although both FA and BRCA proteins are required for ICL repair, each pathway also supports nonoverlapping functions (11,12) that play different roles in how cells respond to treatment with DNA cross-linking agents.…”
mentioning
confidence: 99%
“…Some researchers suggest that BRCA1-A complex decreases end resection activity in processes of HR repair [35,61]. On the contrary, under different experimental conditions, BRCA1-A complex increases HR repair activity [17,18,78]. One possible explanation would be that the BRCA1-A complex can be regulated by different factors in different context.…”
Section: Merit40mentioning
confidence: 89%
“…As a result, MERIT40 is essential for proper DNA damage repair, G2/M checkpoint, and cell survival [19,20]. Recently, it was suggested that MERIT40 is required for ICLs repair pathways, which is independent of BRCA2 [78]. Jiang and colleagues [78] demonstrated that end resection and HR are reduced after ICLs damage in MERIT40-null cells.…”
Section: Merit40mentioning
confidence: 99%
See 1 more Smart Citation
“…The lethality induced by FANCD2 abrogation in BRCA2-deficient cells (Michl et al 2016) can be exploited therapeutically to treat BRCA2-deficient tumors. Similarly, the mediator of RAP80 interactions and targeting subunit of 40 kDa (MERIT40), a subunit of the receptor-associated protein 80 (RAP80) ubiquitin recognition complex involved in the targeting of BRCA1 to DNA damage sites, has recently been implicated in the processing of ICLs and could be an interesting target for anticancer therapy (Jiang et al 2015). Indeed, the increased chromosomal aberrations observed in Merit40-and Brca2-deficient mouse embryonic fibroblasts highlights the relevance of targeting MERIT40 in BRCA2-deficient tumor cells.…”
Section: Novel Therapeutic Approachesmentioning
confidence: 99%